2009
DOI: 10.1111/j.1600-079x.2009.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin downregulates nuclear erythroid 2‐related factor 2 and nuclear factor‐kappaB during prevention of oxidative liver injury in a dimethylnitrosamine model

Abstract: Melatonin has potent hepatoprotective effects as an antioxidant. However, the signaling pathway of melatonin in the induction of antioxidant enzymes against acute liver injury is not fully understood. The study aimed to determine whether melatonin could prevent dimethylnitrosamine (DMN)-induced liver injury through nuclear erythroid 2-related factor 2 (Nrf2) and inflammation. Liver injury was induced in rats by a single injection of DMN (30 mg/kg, i.p.). Melatonin treatment (50 mg/kg/daily, i.p.) was initiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
90
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 54 publications
7
90
1
2
Order By: Relevance
“…Melatonin reduces nf-κB binding in spleen [89]. a number of laboratories report melatonin-induced inhibition of nK-κB activity or inhibition of nf-κB activation [90][91][92][93][94][95][96][97][98][99][100]. these results suggest an interaction of melatonin and the ubiquitin-proteasome system in the activation of nf-κB.…”
Section: Melatonin/ubiquitin Interaction In Brown Fatmentioning
confidence: 51%
“…Melatonin reduces nf-κB binding in spleen [89]. a number of laboratories report melatonin-induced inhibition of nK-κB activity or inhibition of nf-κB activation [90][91][92][93][94][95][96][97][98][99][100]. these results suggest an interaction of melatonin and the ubiquitin-proteasome system in the activation of nf-κB.…”
Section: Melatonin/ubiquitin Interaction In Brown Fatmentioning
confidence: 51%
“…Further, melatonin ameliorates oxidative stress through Nrf2 induction in experimental models of hepatic injury (Osburn et al 2006;Aleksunes and Manautou 2007;Crespo et al 2010;Yang et al 2011). Activation of Nrf2 by melatonin has been described to result in an increased expression of the antioxidant enzyme haem oxygenase-1 (HO-1) and a restriction of hepatic injury (Jung et al 2009;Crespo et al 2010). Although experimental and clinical studies have shown that melatonin restrains oxidative liver injury (Ohta et al 2000;Oz et al 2006), we failed to find any reports on a possible protective effect of melatonin on burn-induced hepatic damage by activation of the Nrf2/HO-1 system.…”
contrasting
confidence: 49%
“…Melatonin induces the expression of antioxidant enzymes such as superoxide dismutase SOD, catalase and gluthatione peroxidase under conditions of elevated oxidative stress (Rodriguez et al 2004), through activation of Nrf2 (Jung et al 2009). Further, melatonin ameliorates oxidative stress through Nrf2 induction in experimental models of hepatic injury (Osburn et al 2006;Aleksunes and Manautou 2007;Crespo et al 2010;Yang et al 2011).…”
mentioning
confidence: 99%
“…Liu et al (28) did not observe increased Nrf2 levels in mouse brain after 12 h of a single 4 Gy radiation dose, but did observe an increase with increasing concentrations of melatonin (1-10 mg/kg). Similarly, following dimethylnitrosamine-induced ROS increase, melatonin (50 mg/kg) administration over 14 days was able to double the nuclear levels of Nrf2 (29).…”
Section: Discussionmentioning
confidence: 99%